2020
DOI: 10.21608/edj.2020.77540
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical study between Tunnel and VISTA approaches for the treatment of multiple gingival recessions with acellular dermal matrix allograft

Abstract: Introduction: Gingival recession results from apical migration of the gingival margin leading to root exposure with esthetical and functional problems. Treatment of gingival recession occurs through variable techniques as laterally positioned flaps, coronally advanced flaps, connective tissue graft, tunnel technique and guided tissue regeneration. Acellular Dermal Matrix allograft (ADM) is a safe alternative to autogenous grafts allows the treatment of multiple adjacent recessions. The tunnel technique (Tun) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other authors have discussed related findings in the literature, for example, Geeti et al 7 The mean WKG in both experiment (VISTA+PRFM membrane group: 2.04 AE 1.36mm) and control group (VISTA+PRF membrane group: 1.5 AE 1.35mm) at six months was not significant in the current study. Mohamed et al (2020), 35 in their study evaluated VISTA + PRF for root coverage and concluded similar results.…”
Section: Discussionmentioning
confidence: 72%
“…Other authors have discussed related findings in the literature, for example, Geeti et al 7 The mean WKG in both experiment (VISTA+PRFM membrane group: 2.04 AE 1.36mm) and control group (VISTA+PRF membrane group: 1.5 AE 1.35mm) at six months was not significant in the current study. Mohamed et al (2020), 35 in their study evaluated VISTA + PRF for root coverage and concluded similar results.…”
Section: Discussionmentioning
confidence: 72%
“…It also minimizes a patient's discomfort because the CTG donor area will heal faster. 16 Gingival wound healing after mucogingival surgery begins with a blood clotting process followed by a granulation phase characterized by a thickening of the gingiva and a maturation phase characterized by creeping attachment. 17 Creeping attachment phenomenon refers to the coronal migration of the gingival margin after mucogingival surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Mansouri et al [ 6 ] compared the VISTA technique with the gold standard coronally advanced flap (CAF) technique using CTG for the treatment of gingival recession defects, which showed higher frequency of root coverage with the VISTA technique as compared to CAF. Mohamed et al [ 7 ] compared the efficacy of the VISTA technique with the tunnel technique (TUN) using acellular dermal matrix (ADM) allograft for gingival recession coverage. The 6-mo follow up results showed a statistically significant difference in favor of the VISTA + ADM technique than the TUN + ADM technique.…”
Section: Introductionmentioning
confidence: 99%